The Effect of Sales Promotion and Knowledge on Impulsive Buying of Online Platform Consumers - Al Mutanafisa, Tasneem; Retnaningsih, Retnaningsih (Journal of Consumer Sciences, 2021)
Impulsive buying is an unplanned purchase decision due to stimulation from the shopping environment. This study aims to analyze the consumer characteristics and sales promotion, knowledge, and impulsive buying and the influence of consumer characteristics, sales promotion, and knowledge on impulsive buying. The study used a cross-sectional study design, which was conducted from December 2019 to January 2020. In this study, respondents were 145 Shopee users who made purchases in the last three months selected purposively. Data were collected by filling out an online questionnaire. The results showed that the length of education was related to sales promotion and knowledge, while income and promotion were related to impulsive buying. Meanwhile, a factor that has a positive effect on impulsive buying is sales promotion. Unplanned online purchases are most often made in the middle of the month, and promotions are the most influential in purchasing decisions.